Enhancing Attention in Medical Students - Sanjit Kumar Kar; Laxmi Shrestha (Journal of Universal College of Medical Sciences, 2024)
ABSTRACT Medical education is a comprehensive and specialized ﬁeld that emphasizes the importance of attention for integrating various pieces of information, development of critical thinking skills and applying knowledge effectively. Enhancement of attentional abilities is essential to keep pace with complicated, critical and commercial social environments. However, the sustained attention is challenged in medical students by various elements, including a rigorous academic curriculum, high levels of stress, and the prevalence of digital distractions. This article has looked at several methods to enhance attention in medical education including improving attentional abilities in students, active learning strategies, and utilization of technology. Furthermore, the article discusses assessment methods for attention, including psychological tests, cognitive tasks, and self-report questionnaires, to identify areas needing improvement and direct interventions. In conclusion, enhancing attention in medical students is a multifaceted challenge that requires a comprehensive approach. By understanding the factors that affect attention and implementing evidence-based strategies, students can better prepare themselves to gather knowledge more effectively and educators can help students to achieve better learning outcomes and prepare them for the demands of their future careers.